Radiological follow-up results of untreated anterior disc displacement without reduction in adults. Issue 3 (March 2016) - Zhuo, Z.; Cai, X.Y.
Abstract: The aim of this study was to assess the radiographic changes in untreated adults with bilateral anterior disc displacement without reduction. A cohort study was designed to compare the bone changes, effusion, disc configuration, and pseudo-disc changes on two magnetic resonance images obtained at least 24 months apart. Twenty-eight patients (22 female, six male) with a mean age of 33.1 years (range 20–57 years) were included. The mean interval between the initial visit and the follow-up visit was 36.2 months. At the initial visit, the frequencies of bone changes, effusion, disc deformation, and pseudo-disc changes were 51.79%, 35.71%, 100%, and 0%, respectively. At follow-up, the frequency of effusion had decreased significantly. The frequency of bone changes had increased significantly to 75%, but newly formed cortical bone was present in five condyles. All discs remained deformed. Pseudo-disc changes were detected in five joints. Over a long period of observation, there was a significant decrease in effusion and a significant increase in bone changes. However, some adaptive changes occurred.